Supply and demand situations for major crops and food items in Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
This study explored historical food availability/supply and the market demand for food. Secondary data was used for analyzing demand-supply gap. The average growth in rice production was 2.9% per year in 1971/72 to 2008/09, of which 93% was contributed by yield growth. The overall growth rate of area under food grain was 0.3% in 1971/72 to 2008/09. The overall food grain production growth rate is higher than population growth rate from 1971/72 to 2008/09. The own price and income elasticities of rice were -0.108 and 0.199 respectively. It was projected that upto 2021, the annual demand for food exceed the supply of food which were -0.28% for rice and -1.76% for wheat. That implies the demands are greater than the supplies for both crops. Keywords: Food supply and demand; Price and income elasticities DOI: 10.3329/jbau.v8i1.6405J. Bangladesh Agril. Univ. 8(1): 91-102, 2010